Penerapan Disiplin Positif Dalam Meningkatkan Karakter Islami Peserta Didik MTs NU Sindujoyo - Adinda Nurrul Fajriani; Nisrina Zacky Salsabila (Tadrisuna : Jurnal Pendidikan Islam dan Kajian Keislaman, 2025)
This research is motivated by the crisis of character and discipline of students in the digital era, such as declining manners and increasing violations of discipline in madrasas. Traditional disciplinary approaches that are punitive have proven to be less effective and can have a negative impact. The purpose of this study is to find out positive discipline in the formation of the Islamic character of students at MTs NU Sindujoyo, to find out the application and impact of positive discipline on the Islamic character of students at MTs NU Sindujoyo and the impact of positive discipline on the Islamic character of students at MTs NU Sindujoyo. In the study, a participatory qualitative method was used. This is to help researchers in exploring and analyzing a phenomenon in a certain context in more depth. So this study shows that positive discipline at MTs NU Sindujoyo is implemented through a point system that includes five criteria (behavior, craftsmanship, neatness, cleanliness, and appreciation). The implementation strategy includes habituation of religious activities (such as dhuha and istighosah prayers), teacher examples, persuasive approaches through dialogue and reflection when violations occur, and providing positive reinforcement. The impact of this implementation can be seen as significant in improving students' religious behavior, growing a sense of responsibility in doing assignments and pickets, and the formation of positive social attitudes such as honesty, good manners, and concern between friends. Based on the findings, it can be concluded that the application of positive discipline at MTs NU Sindujoyo has proven effective in improving the Islamic character of students. This approach successfully fosters internal awareness and responsibility through habituation, exemplary, and persuasive approaches structured in a point system. The positive impact is reflected in improved religious behavior, responsibility, and social attitudes, which overall creates a more harmonious and conducive learning environment.